DIDACTIC FEATURES OF MORAL TEACHINGS IN YUSUF KHOS HAJIB’S EPIC POEM “KUTADGU BILIG” - Abdufattoyeva Adibaxon Zafarjon kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the didactic features of moral teachings expressed in Yusuf Khos Hajib’s epic poem Kutadgu Bilig. The work explores such issues as human perfection, morality, wisdom, justice, contentment, parental responsibility, child upbringing, speech etiquette, social relations, and the idea of the perfect human being in a poetic and didactic manner. Kutadgu Bilig is not only a major literary monument reflecting the socio-political and philosophical views of its time, but also an important didactic source that serves the spiritual and moral education of the younger generation. The article examines the educational content of the epic, the methods of expressing moral categories, the system of symbolic images, and the significance of moral counsels in the modern educational process. In addition, several couplets from the work are analyzed, and the educational ideas presented in them are interpreted in connection with contemporary pedagogical views.